2020
DOI: 10.1002/jlb.1ma0420-634r
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged neutrophil survival at necrotic sites is a fundamental feature for tissue recovery and resolution of hepatic inflammation

Abstract: Neutrophils were classically described as powerful effectors of acute inflammation, and their main purpose was assumed to be restricted to pathogen killing through production of oxidants. As consequence, neutrophils also may lead to significant collateral damage to the healthy tissues, and after performing these tasks, these leukocytes are supposed to die within tissues. However, there is a growing body of evidence showing that neutrophils also play a pivotal role in the resolution phases of inflammation, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
4
8
0
Order By: Relevance
“…The tissue damage caused by APAP overdose led to an impairment in liver function measured by an increase in indocyanine green (ICG) in the serum due to a reduced depuration rate 24h after APAP administration ( Figure 1F ) . Following 72h, the serum ICG levels were reduced to similar levels found in the non-treated control group ( Figure 1F ) in line with the regenerative process of the disease ( 24 , 39 , 40 ). To get an insight into the impact of the inflammatory response in the myeloid cell compartment, we assessed the influx of neutrophils in the liver and changes in the myeloid cell populations, including liver resident Kupffer cells (KCs), monocyte subsets ( Supplementary Figure 1A ) .…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The tissue damage caused by APAP overdose led to an impairment in liver function measured by an increase in indocyanine green (ICG) in the serum due to a reduced depuration rate 24h after APAP administration ( Figure 1F ) . Following 72h, the serum ICG levels were reduced to similar levels found in the non-treated control group ( Figure 1F ) in line with the regenerative process of the disease ( 24 , 39 , 40 ). To get an insight into the impact of the inflammatory response in the myeloid cell compartment, we assessed the influx of neutrophils in the liver and changes in the myeloid cell populations, including liver resident Kupffer cells (KCs), monocyte subsets ( Supplementary Figure 1A ) .…”
Section: Resultssupporting
confidence: 70%
“…Acetaminophen (APAP) is one of the most common causes of human acute liver injury and acute liver failure that can result in death ( 24 ). Here, we used a well-established mouse model of acute liver injury (ALI) ( 16 , 33 , 39 ) to investigate alterations in the myeloid cell compartment during liver damage. To induce ALI, C57BL/6 female mice were fasted for 15h and given oral gavage with 600 mg/kg of APAP diluted in warm saline ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the contribution of placental inflammation induced by FPR2 to the pathophysiology of FGR had been investigated. However, the increased expression of FPR2 was found in some diseases, such as hepatic inflammation, autoimmune encephalomyelitis, neonatal hypoxia‐ischaemic injury 36‐38 . The current study showed that the expression of FPR2 in placental tissues of CAM patients, who were carefully selected using strict clinical standards and underlying pathology, was significantly higher than PTB women without CAM.…”
Section: Discussionmentioning
confidence: 49%
“…In support of this concept, IL-1R2 was described as a critical molecule in resolving liver inflammation (66). In particular, neutrophils up-regulated IL-1R2 in a liver injury model and contributed to protecting mice from hepatic deterioration, as confirmed by the adoptive transfer of this subset in the early stage of liver damage (66).…”
Section: Il-1r2 In Sterile Inflammationmentioning
confidence: 96%
“…In contrast, IL-1R2-deficiency did not affect severity and mortality following acute administration of IL-1b or LPS, suggesting that IL-1R2 is primarily involved in regulating local inflammation (65). In support of this concept, IL-1R2 was described as a critical molecule in resolving liver inflammation (66). In particular, neutrophils up-regulated IL-1R2 in a liver injury model and contributed to protecting mice from hepatic deterioration, as confirmed by the adoptive transfer of this subset in the early stage of liver damage (66).…”
Section: Il-1r2 In Sterile Inflammationmentioning
confidence: 98%